(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The aim of the research was to determine the role of content marketing in achieving sustainable customer value among a sample of Asiacell app users. The study adopted content marketing as an independent variable, as well as addressing sustainable customer value as a dependent variable. Thus, the research problem was formulated with the following question: "To what extent does content marketing contribute to achieving sustainable customer value?" To answer this question, a number of hypotheses were formulated and a questionnaire was designed to validate them. The study population consisted of faculty, employees, and students at the College of Management and Economics in the University of Mosul. A purposive sample of 175 individuals was drawn from the population of the study, with 13 invalid questionnaires excluded from the analysis, leaving 162 valid responses. Various statistical methods were employed using SPSS V26 and included: frequencies, percentages, means, standard deviations, Pearson correlation coefficient, and simple linear regression. The study revealed several key results, including a significant positive effect of content marketing on sustainable customer value and significant positive effects of each dimension of content marketing (relevance, credibility, emotion, value, and attractiveness) on sustainable customer value. The study also provided suggestions, emphasizing the Asiacell company should focus on content marketing due to its significant role in achieving sustainable customer value through its dimensions (relevance, credibility, emotion, value, and attractiveness), stressing the necessity for electronic content to be credible, relevant attractive, and meeting customer needs for all user segments at all ages.